Increasing time to treatment initiation for head and neck cancer: An analysis of the National Cancer Database. Issue 8 (9th December 2014) - Murphy, Colin T.; Galloway, Thomas J.; Handorf, Elizabeth A.; Wang, Lora; Mehra, Ranee; Flieder, Douglas B.; Ridge, John A.
<x xml:space="preserve">Abstract</x> BACKGROUND The objective of this study was to identify trends and predictors of the time to treatment initiation (TTI) for patients with head and neck squamous cell carcinoma (HNSCC). METHODS The National Cancer Database (NCDB) was reviewed for the following head and neck cancer sites: oral tongue, oropharynx, larynx, and hypopharynx. TTI was defined as the number of days from diagnosis to the initiation of definitive treatment and was measured according to covariates. Significant differences in the median TTI across each covariate were measured using the Kruskal‐Wallis test, and the Spearman test was used to measure trends within covariates. For multivariate analysis, a zero‐inflated, negative, binomial regression model was used to estimate the expected TTI, which was expressed in the predicted number of days; and the Vuong test was used to identify the predictors of TTI. RESULTS In total, 274, 630 patients were included. Between 1998 and 2011, the median TTI for all patients was 26 days, and it increased from 19 days to 30 days (P < .0001). Treatment with chemoradiation (CRT) (P < .0001), treatment at academic facilities (P < .0001), and stage IV disease (P < .0001) were associated with increased TTI. TTI significantly increased for each disease stage (P < .0001), treatment modality (P < .0001), and facility type (P < .0001) over time. In addition, patients became more likely to transition care between facilities after diagnosis for treatment initiation (P < .0001) over time. On multivariate analysis, treatment at academic facilities (33 days), transitioning care (37 days), and receipt of CRT (39 days) predicted for a longer TTI. CONCLUSIONS TTI is rising for patients with HNSCC. Those who have advanced‐stage disease, receive treatment with CRT, are treated at academic facilities, and who have a transition in care realized the greatest increases in TTI. Cancer 2015;121:1204–1213. © 2014 American Cancer Society.